Use of a conditional MyoD transcription factor in studies of MyoD trans-activation and muscle determination. - Hollenberg, S M (1993)
DNA sequences encoding the hormone-binding domains of several steroid hormone receptors were fused in frame to the MyoD gene. When the gene for this chimeric protein was expressed in NIH 3T3 or 10T1/2 fibroblasts, these cells displayed hormone-dependent induction of myogenesis. Our experiments focused on cell lines expressing estrogen receptor-MyoD chimeras. Induction of these lines in the presence of estradiol and an inhibitor of protein synthesis, cycloheximide, resulted in the activation of the endogenous myogenin gene but did not activate the muscle-specific creatine kinase or cardiac alpha-actin gene. This result suggests that MyoD is not a "direct" activator of these downstream myogenic genes but must first activate myogenin as an intermediary. Once muscle is induced by estrogen receptor-MyoD the muscle phenotype is very stable and does not need the continued presence of estradiol for its maintenance.